Sosialisasi Pengelolaan Wisata Berkelanjutan Sebagai Peluang Peningkatan Ekonomi Masyarakat Dalam Upaya Mendukung Konservasi Keanekaragaman Hayati Di Wilayah Pantai - Elfa Yeni; Nurjannah, Nurjannah; Asmawati (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2025)
This community service activity aims to increase the capacity of the community regarding coral reef ecotourism in order to improve the economy of the Lamreh village community, Mesjid Raya District, Aceh Besar Regency, Aceh through FDG (Focus Group Discussion) activities and beach clean-up actions. This activity involves the community and youth of Lamreh village. The results of this activity show that in the FGD it was known that there was an understanding of the community regarding the importance of maintaining coral reefs for the sustainability of tourism which can improve the community's economy. while in the beach clean-up action, tourist signs and trash bins were installed for beach cleanliness at the beach location.